Screening of cowpea varieties for resistance to brown blotch fungal disease (2006)
Seventy-one cowpea varieties were screened in the field out of which nine resistant varieties were selected and these were further evaluated for resistance to cowpea brown blotch disease caused by Collectorichnm capsicl under artificial inoculation. The results showed that the cowpea variety IT95k- 193-12 appeared to be the most resistant to brown blotch disease. Artificial inoculation seemed to be more effective in identifying resistant genotypes as most of the cowpea varieties with moderate resistance in the field were highly susceptible under artificial inoculation.